Pectin-based injectable and biodegradable self-healing hydrogels for enhanced synergistic anticancer therapy. (1st September 2021) - An, Heng; Yang, Yan; Zhou, Ziwei; Bo, Yunyi; Wang, Yong; He, Yingna; Wang, Dong; Qin, Jianglei
Abstract: We report a new injectable and biodegradable self-healing hydrogel that shows enhanced anticancer drug release property. The hydrogel was prepared based on biodegradable pectin aldehyde (pectin-CHO) and acylhydrazide functionalized polymer poly(N-isopropylacrylamide- stat -acylhydrazide) P(NIPAM- stat -AH). Due to the dynamic nature of acylhydrazone bonds, the hydrogel exhibits self-healing behavior and its mechanical properties can be regulated by the weight ratio of P(NIPAM- stat -AH) to pectin-CHO. The in vitro and in vivo experiments show the hydrogel has not only good biocompatibility and biodegradability, but also decreases the toxicity of the drugs to living body and exhibits controlled drug release behavior as synergetic anti-tumor drug delivery carriers. The results demonstrate that the pectin-based self-healing hydrogels are injectable, biodegradable, and self-healable that is promising for localized anti-tumor therapy. Statement of significance: Injectable hydrogels with self-healing property and biodegradability are excellent candidates as drug loading and release carrier for biomedical applications. However the pectin as a biobased material is always neglected in self-healing hydrogel preparation. In this study, we fabricated biodegradable self-healing hydrogels from aldehyde group bearing pectin (pectin-CHO) and thermo-responsive copolymer of P(NIPAM- stat -AH). The hydrogel showed sustained drug release behavior, good biocompatibility and biodegradability both in vitro and in vivo . The in vivo experiment shows that the hydrogel with coloaded DOX and CA4 has synergetic therapy to CT26 tumors and this kind of biodegradable hydrogel has great potential application in antitumor therapy. Graphical abstract: Image, graphical abstract